2008
DOI: 10.1038/sj.bjc.6604272
|View full text |Cite
|
Sign up to set email alerts
|

Intra-arterial chemoradiotherapy for locally advanced oral cavity cancer: analysis of therapeutic results in134 cases

Abstract: The objective of this study was to investigate the therapeutic results of arterial injection therapy via the superficial temporal artery for 134 cases of stages III and IV (M0) oral cavity cancer retrospectively, and to clarify the prognostic factors. We administered intraarterial chemoradiotherapy by continuous infusion of carboplatin in 65 cases from January 1993 to July 2002. Systemic chemotherapy was performed on 26 cases at the same time. We administered intra-arterial chemoradiotherapy by cisplatin with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
53
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 21 publications
1
53
0
1
Order By: Relevance
“…Fuwa et al found and improved survival in their study of 134 patients with advanced OCC using intra-arterial CRT. 16 Although there were 38 primary site relapses with this regimen (and only nine were successfully salvaged), OS at 3 years was 53.9%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fuwa et al found and improved survival in their study of 134 patients with advanced OCC using intra-arterial CRT. 16 Although there were 38 primary site relapses with this regimen (and only nine were successfully salvaged), OS at 3 years was 53.9%.…”
Section: Discussionmentioning
confidence: 99%
“…16,[18][19][20][21][22] Clinically meaningful and/or standardized definitions of ORN differ from paper to paper and consist of various multistep scales and scoring systems based on each author's notion of risk factors, signs, or symptoms. These are meant to help organize our understanding of clinically significant ORN, but the ORN student may be left with some confusion.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, it makes sense to superselectively catheterize into the multiple arteries that feed the tumor in advanced cases. Catheterization into the LA, FA, and MA from the STA is quite available because the STA is technically easy to expose 9,11,14 . Furthermore, the OA is an also a useful artery for achieving catheter placement in the FA or LA, though it is relatively difficult to expose because it exists deep from the skin surface 20 .…”
Section: Catheterizationmentioning
confidence: 99%
“…Catheterization via the STA or OA enabled the retention of the catheter for daily concurrent chemoradiotherapy, which is likely to be more effective than 4 sequential chemoradiotherapy 10 . Fuwa et al 11,12 reported excellent therapeutic results for this therapy in terms of local control of advanced oral cancer; indeed, their therapeutic results were not inferior to those of surgery. However, most advanced tumors are nourished by multiple arteries and have a high incidence of regional lymph node metastasis.…”
mentioning
confidence: 99%
“…Recent research revealed that chemo-radiation therapy (CRT) seems to be effective for advanced head and neck squamous cell carcinomas (head and neck SCC) including oral squamous cell carcinomas (oral SCC) (Robbins et al 2005;Doweck et al 2008;Fuwa et al 2008;Stenson et al 2010). However, the treatment strategies have not yet been established for oral SCC, excluding tongue SCC, such as SCC in buccal mucosa, gingiva, hard palate and oral floor, because of the rare incidence (Ariyoshi et al 2008).…”
mentioning
confidence: 99%